2014
DOI: 10.3341/kjo.2014.28.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Korean Guidelines for the Diagnosis and Management of Dry Eye: Development and Validation of Clinical Efficacy

Abstract: PurposeTo evaluate the clinical efficacy of newly developed guidelines for the diagnosis and management of dry eye.MethodsThis retrospective, multi-center, non-randomized, observational study included a total of 1,612 patients with dry eye disease who initially visited the clinics from March 2010 to August 2010. Korean guidelines for the diagnosis and management of dry eye were newly developed from concise, expert-consensus recommendations. Severity levels at initial and final visits were determined using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 17 publications
0
55
0
Order By: Relevance
“…Secondary SS subjects were excluded from the SS group. DES group included subjects complaining of dry eye symptoms and less than 10 seconds of tear break up time (TBUT) which was defined as environmental dry eye syndrome by the Korean Guidelines [24]. DES group was also confirmed to have no existing auto-antibodies or rheumatology-related diseases.…”
Section: Subjectsmentioning
confidence: 99%
“…Secondary SS subjects were excluded from the SS group. DES group included subjects complaining of dry eye symptoms and less than 10 seconds of tear break up time (TBUT) which was defined as environmental dry eye syndrome by the Korean Guidelines [24]. DES group was also confirmed to have no existing auto-antibodies or rheumatology-related diseases.…”
Section: Subjectsmentioning
confidence: 99%
“…One previous report demonstrated that carbomer-based lipid-containing gel (Liposic Gel) is effective for the treatment of dry eye syndrome. 14 Tear film has 3 layers: aqueous, mucin, and lipid. 4 Each has a different role in maintaining homeostasis of the ocular surface and tear film stability.…”
Section: Discussionmentioning
confidence: 99%
“…Data from symptoms, tBUT, ocular surface staining grades, and Schirmer I test without anesthesia values were combined to determine each dry eye level according to the Korean Corneal Disease Study Group guidelines approach. 14 Safety profile was assessed by patient reporting of adverse events. Visual acuity, intraocular pressure, and slitlamp examination of the anterior segment were determined at the baseline and after 4 weeks of treatment.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…In the report, they define DED as ''a disease of the ocular surface that is associated with tear film abnormalities.'' 18 They proposed diagnostic criteria involving one or more symptoms (either irritating or visual symptoms), plus at least one objective sign including either ocular surface staining or tear film instability.…”
Section: Historical Overview Of Definition and Diagnostic Criteria Ofmentioning
confidence: 99%